Observation or insight? Unraveling the impact of characters' image on interpersonal communication in contemporary Chinese tv series - Dai, Haocheng; Kasimon, Diyana Nawar; Ang, Lay Hoon (Redfame Publishing, 2024)
A salient determinant of effective interpersonal communication resides in the cultivation of a positive personal image. The intricate interplay between self-image, individual behaviors, and communication abilities highlights the far-reaching influence of personal perception on social interactions. In the contemporary landscape of Chinese television series, exemplified by the production ‘Nothing but Thirty’, a deliberate effort is made to depict characters that embody the evolving roles of women in modern society. Drawing from relevant literature, this study conducts a comprehensive analysis of characters’ image in ‘Nothing but Thirty’, examining content such as appearance, language, non-verbal cues (body language), and varied scene settings. Adopting a rigorous qualitative case study methodology and leveraging content analysis grounded in the coordinated management of meaning theory and social exchange theory, the research aims to dissect the nuanced dynamics of interpersonal communication as portrayed in the series. The findings illuminate that the dynamic characterizations in contemporary Chinese TV series function as reflective mirrors, capturing the intricate layers of modern interpersonal communication and societal intricacies. This narrative analysis extends beyond the purview of conventional storytelling, offering a scholarly exploration of the intricate fabric of human interaction.